Clare Duignan - Duignan, Clare (Irish Journal of Arts Management and Cultural Policy, 2015)
Claire Duignan, formerly a senior executive with the Irish broadcasting service (RTE) and an experienced board member, spoke about the need for arts organisations to diversify their sources of funding in times of recession and lamented the absence of broadcasters from the wider debate about cultural policy Thank you very much everyone and it’s very nice to be here this morning. I am afraid I am about to lower the tone and talk about money and finance. In particular, I want to talk about public funding for the arts and the cuts that everyone has been living with the last couple of years.